Online news production, consumption and immediacy: the remediation perspective - Bahiyah Omar (Penerbit Universiti Kebangsaan Malaysia, 2017)
Evidence suggests that media displacement theory has limitation to explain the current development in news industry. This paper turns to the work of Bolter and Grusin on remediation which promotes the idea that old media are being transformed into new digital forms. Anchoring on this idea, this paper offers ways of understanding the processes in which online news sources repurpose print news for digital spaces via remediation. Three processes were identified; (1) borrowing the content and reusing it in a different format, (2) borrowing the format only and not the content, and (3) absorbing the older medium in its entirety. The paper also explores users’ experience with new news media and suggests that greater interactivity and user control in online environment indicate the experience of immediacy. To achieve immediacy is the goal of all media, and its manifestation ranges from an improved experience to a sense of being there (or presence) in media use. Linking remediation and literature in journalism studies, this essay contests the straightforward definition of news immediacy and introduces a theoretically driven concept focusing on a sense of presence in news consumption. The dimension of immediacy adds to our knowledge of the complementary use of online and print news media, and is central to the issue of media survival and competition in today’s digital age.